Cultural Diplomacy and Brancusi’s Reception in the Digital Age in Romania - Stanciu, Nicolae (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2020)
The internet and media resources have opened new opportunities for digital cultural diplomacy and management of culture. Theoretically an ideal choice for cultural diplomacy, Constantin Brancusi’s reputation as a representative for government agency has suffered a crisis of reception. A Romanian-born and French-adopted sculptor, Brancusi has become a symbol of folklore and mythology but also a great, internationally recognized sculptor. This has been due to the existence of preferred or fixed models of desigining projects instead of involving teams of different backgrounds and incorporating cultural concepts in the political discourse. Approaching the topic with concepts of cultural diplomacy, media anthropology, heritage and online discourse, this case study deals with media events of cultural diplomacy broadcasted online in present day Romania. It emphasizes the potential that lies in cultural management and the important role of team spirit in designing public cultural policies and implementing projects.